If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -14 = 6x + 37 Reorder the terms: -14 + 9x = 6x + 37 Reorder the terms: -14 + 9x = 37 + 6x Solving -14 + 9x = 37 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -14 + 9x + -6x = 37 + 6x + -6x Combine like terms: 9x + -6x = 3x -14 + 3x = 37 + 6x + -6x Combine like terms: 6x + -6x = 0 -14 + 3x = 37 + 0 -14 + 3x = 37 Add '14' to each side of the equation. -14 + 14 + 3x = 37 + 14 Combine like terms: -14 + 14 = 0 0 + 3x = 37 + 14 3x = 37 + 14 Combine like terms: 37 + 14 = 51 3x = 51 Divide each side by '3'. x = 17 Simplifying x = 17
| 2[1-3(x+2)]=x | | 90=15h | | -14=-5x+13 | | 14-2x+5=-2x+9 | | 7x(4-2)= | | 0.02(y-7)+0.10y=0.04y-0.09(10) | | 45g=720 | | -3(-6x-2)=-30 | | -23+x+28=x+5 | | X^2+47x+210=0 | | 5r+2=-1+4r | | 46.50n-15=5.25 | | 5x+14-2x=9+3(x+2) | | (5x-64)=3x | | -8(v*3)-7v=-4+10(1-v) | | 9k-21=3(k-7)+6k | | 25(35h)=40h | | -23+x+28= | | -2x-8=8x+1 | | 3x(2xy^2+4y^3)=V | | (4x+3)(3x-5)=(4x-3)(3x+5) | | 12x+50=7x-40 | | 5x-5=5(x+7) | | 6+13=6+(n+5) | | .12222= | | 5c+c=78 | | -5x+13=14 | | -2=20x | | 6n^2-18n-168=0 | | 12m-15=-3 | | 3x-0.4=1.4 | | Y+28=x+5 |